Differences in Patterns of Preoperative Assessment Between High, Intermediate, and Low Volume Surgeons When Performing Hysterectomy for Uterovaginal Prolapse. Issue 1 (January 2016) - Pulliam, Samantha J.; Morgan, Daniel M.; Guaderrama, Noelani; Guire, Kenneth; Adam, Rony A.
Abstract : Objective: The aim of the study was to determine whether surgeon case volume is associated with preoperative evaluation of pelvic organ prolapse before a hysterectomy for uterovaginal prolapse including a complete objective evaluation of prolapse (Baden-Walker or Pelvic Organ Prolapse Quantification), an offer of nonsurgical options for therapy (pessary), and a preoperative assessment of urinary incontinence Methods: We performed a multicenter retrospective review of hysterectomies done for uterovaginal prolapse at 4 hospital systems between January 1, 2008 and December 31, 2011. The number of hysterectomies per surgeon for 4 years was evaluated to establish low-volume (⩽10 cases), intermediate-volume (11–49 cases), and high-volume (≥50 cases) groups. Rates of preoperative standardized prolapse evaluations, offer of pessary, and evaluation of stress urinary incontinence were determined by chart review of 15% of the hysterectomy cases. Adjustment was made in a logistic regression model for age, race, insurance status, and prolapse size. Results: Three hundred one surgeons performed 4238 hysterectomies for prolapse during the study period. Rates of preoperative assessment by standardized pelvic examination differed between high-, intermediate-, and low-volume surgeons (91.2% vs 61.3% vs 48.8%, respectively), as did offer of a pessary (86.5% vs 71.9% vs 69.9%, respectively) and preoperative stress test for urinary incontinence (93.5% vs 72.8% vs 63.5%, respectively). Regression analysis revealed that high-volume surgeons were more likely than intermediate- or low-volume surgeons to perform a standardized pelvic examination, offer a pessary, or perform preoperative evaluation for urinary incontinence. Conclusions: High-volume surgeons were more likely than low-volume surgeons to perform a standardized preoperative pelvic examination, offer a pessary, and evaluate stress urinary incontinence. Abstract : When evaluating a patient before hysterectomy for pelvic organ prolapse, high-volume surgeons are more likely than low-volume surgeons to perform a standardized pelvic examination, offer a pessary, and perform a stress test to evaluate urinary incontinence.